Stephen L. Brock, Action and Conduct. A Thomistic Study. Athenaeum Romanum Sanctae Crucis. Facultas Philosophiae. Romae 1992. 278 páginas - Crespo, Ricardo F. (1995)
Fil: Crespo, Ricardo F. Universidad Nacional de Cuyo; Argentina